2012
DOI: 10.1007/s10433-012-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between received social support and positive and negative affect: evidence for age differences from a daily-diary study

Abstract: Recent evidence suggests negative associations between received social support and emotional well-being. So far, these studies mainly focused on younger adults. Quantity and quality of social support changes with age; therefore, this study investigated whether there are age differences regarding the association between received social support and positive affect (PA) and negative affect (NA). Moreover, it was tested whether these age effects might be due to a differential effectiveness of different sources of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
6
26
0
2
Order By: Relevance
“…However, reciprocity [46-49] and the specific source of the support [50,51] may be considered as additional factors affecting this issue. Understanding support and negative outcomes must take into account many dimensional pathways [50], not all of which could be addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, reciprocity [46-49] and the specific source of the support [50,51] may be considered as additional factors affecting this issue. Understanding support and negative outcomes must take into account many dimensional pathways [50], not all of which could be addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The between‐person effects of social stress on negative affect (SOCSTRESSBW j ) were then accounted for by adding this variable as a predictor of the intercept on Level 2. This method allows for the disaggregation of within‐person and between‐person effects of social stress on negative affect (Mroczek & Almeida, ; Raudenbush & Bryk, ; Scholz, Kliegel, Luszczynska, & Knoll, ). Prior day negative affect (NEGAFFECT t– 1 ) was included as a Level 1, within‐person covariate to account for the potentially confounding effects of continuity of negative affect across days.…”
Section: Methodsmentioning
confidence: 99%
“…Social interaction has a negative impact on negative affect [59]. Many scholars have demonstrated that social support could affect the individual's emotional health [60][61][62][63][64], the other researchers further consider that social support is significantly positively correlated with positive affect and negatively related to negative affect [65]. It is believed that social capital, such as social support, can directly improve a positive experience.…”
Section: Community Social Capital and Emotion Experiencementioning
confidence: 99%